The organization of exhibitions as a kind of scientific-creative activity of the future artists-teachers (Pedagogy of Higher and Secondary Education, 2006)
In the article a question is considered about the role of exhibition activity in the system of artistically-pedagogical education and councils are expounded of organization of artistic exhibition.
Keywords: exhibition; display; project; plan